2003
DOI: 10.1002/mus.10595
|View full text |Cite
|
Sign up to set email alerts
|

Preserved cutaneous silent periods in severe entrapment neuropathies

Abstract: Noxious digital nerve stimulation during isometric contraction of hand muscles leads to transient suppression of the electromyographic activity, the so-called cutaneous silent period (CSP), which is mostly due to a spinal reflex mediated by A-delta fibers. We investigated two patients with carpal tunnel syndrome (CTS) and two patients with ulnar entrapment at the elbow (UNE), in whom routine sensory conduction studies failed to document afferent fiber continuity across the lesion site. In three patients, motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…Similarly, Svilpauskaite et al [14] showed that only transection of a peripheral nerve, but not severe entrapment, abolished the CSP. In agreement with previous reports that demonstrated relative preservation of CSP responses in other peripheral nerve syndromes [2,5,7,14], we now provide evidence that the CSP is not affected by cervical radiculopathies. Our findings are also congruous with the observation that many patients seeking medical treatment for cervical radiculopathy do not manifest features of overt axonal loss.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, Svilpauskaite et al [14] showed that only transection of a peripheral nerve, but not severe entrapment, abolished the CSP. In agreement with previous reports that demonstrated relative preservation of CSP responses in other peripheral nerve syndromes [2,5,7,14], we now provide evidence that the CSP is not affected by cervical radiculopathies. Our findings are also congruous with the observation that many patients seeking medical treatment for cervical radiculopathy do not manifest features of overt axonal loss.…”
Section: Discussionsupporting
confidence: 93%
“…Aurora et al [2] reported normal CSP onset latencies in mild to moderate carpal tunnel syndrome, and concluded that small fiber dysfunction occurred late in the course of this compressive neuropathy. Kofler et al [5] found that preserved CSPs may serve to document residual nerve continuity in severe entrapment neuropathies when fast-conducting fibers were so compromised that their continuity could not be detected by standard electrodiagnostic techniques. Similarly, Svilpauskaite et al [14] showed that only transection of a peripheral nerve, but not severe entrapment, abolished the CSP.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also in line with several clinical observations showing that the CSP is preserved in severe entrapment neuropathies, whereas routine nerve conduction studies have failed to demonstrate residual afferent nerve fiber continuity. 9 Although we found it unsuitable for assessing nociceptive pathway function in patients with neuropathic pain, the CSP has proven useful for both experimental and clinical purposes. The CSP has been used to measure descending influences on spinal excitability of inhibitory pathways in patients with basal ganglia and pyramidal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…2,20 Peripheral neuropathy usually manifests with sensory disturbances including hypesthesia, paresthesia, and neuropathic pain associated with nociceptive pathway damage. 10 Although some studies have used the CSP to investigate nociceptive pathway function in patients with peripheral neuropathy, 9,12,18 others have questioned whether the CSP is a true nociceptive response. 7,16 Hence, the diagnostic value of the CSP for assessing nociceptive pathway function in patients with neuropathic pain is still debated.…”
mentioning
confidence: 99%
See 1 more Smart Citation